PENGGUNAAN MODEL PEMBELAJARAN TALKING STICK UNTUK MENINGKATKAN PRESTASI BELAJAR MATEMATIKA PADA SISWA SMK - Imrona Hayati (STAI AL FALAH Banjarbaru, 2019)
The aim of this study was to describe the application of Talking Stick learning model to increase the learning achievement of students at SMKN 2 Singosari Malang. The type of this research is action research with the data source EI (Industrial Electronics) class XI-SMKN 2 Singosari totaling 34 students. The reason of choosing EI class XI-SMKN 2 Singosari as the subject was a situation in which the students have many problems while learning mathematics, as the sample students solving the problems with less appropriate and many difficulties to solving the everyday problems related to the competence. Based on the result of this study, the conclusion was the application of Talking Stick learning model proved to increase the learning achievement of SMKN 2 Singosari Malang students. That cause application of Talking Stick learning model very recommended for teachers in order to get maximal learning result. Keywords: Learning Mathematics, Talking Stick Learning Model, Increase, Learning Achievement.